The Effects of Flaxseed Oil Omega-3 Fatty Acids Supplementation on Metabolic Status of Patients with Polycystic Ovary Syndrome: A Randomized, Double-Blind, Placebo-Controlled Trial - Mirmasoumi, Golara; Fazilati, Mohammad; Foroozanfard, Fatemeh; Vahedpoor, Zahra; Mahmoodi, Samaneh; Taghizadeh, Mohsen; Esfeh, Nazanin Kazemi; Mohseni, Maryam; Karbassizadeh, Hassan; Asemi, Zatollah (Experimental and Clinical Endocrinology & Diabetes, 2017)
Objective This study was conducted to evaluate the effects of flaxseed oil omega-3 fatty acids supplementation on metabolic status of patients with polycystic ovary syndrome (PCOS).Methods This randomized double-blind, placebo-controlled trial was conducted on 60 women with PCOS according to the Rotterdam criteria aged 18–40 years old. Participants were randomly assigned into two groups to receive either 1,000 mg flaxseed oil omega-3 fatty acids (n=30) or placebo (n=30) twice a day for 12 weeks. Metabolic, endocrine, inflammatory factors were quantified at baseline and after the 12-week intervention.Results After the 12-week intervention, compared to the placebo, flaxseed oil omega-3 supplementation significantly decreased insulin values (−2.6±7.7 vs.+1.3±3.9 µIU/mL, P=0.01), homeostasis model of assessment-estimated insulin resistance (−0.7±1.7 vs.+0.3±0.9, P=0.01), mF-G scores (−1.2±1.7 vs. -0.1±0.4, P=0.001), and increased quantitative insulin sensitivity check index (+0.01±0.02 vs. −0.01±0.02, P=0.01). In addition, supplementation with flaxseed oil omega-3 resulted in significant decreases in serum triglycerides (−5.1±20.9 vs.+9.7±26.1 mg/dL, P=0.01), VLDL-cholesterol (−1.0±4.2 vs.+1.9±5.2 mg/dL, P=0.01) and high-sensitivity C-reactive protein (hs-CRP) (−1.6±3.1 vs.+0.2±1.5 mg/L, P=0.004) compared to the placebo. We did not see any significant effect of flaxseed oil omega-3 supplementation on hormonal and other lipid profiles, and plasma nitric oxide levels.Conclusions Overall, flaxseed oil omega-3 supplementation for 12 weeks in women with PCOS had beneficial effects on insulin metabolism, mF-G scores, serum triglycerides, VLDL-cholesterol and hs-CRP levels, but did not affect hormonal and other lipid profiles, and plasma nitric oxide levels.
Keywords: Flaxseed oil supplementation; metabolic status; polycystic ovary syndrome